Molecular evidence of polyphyletism in the plant genus Carum L. (Apiaceae) - Alessio Papini; Francesca Banci; Enio Nardi (Genetics and Molecular Biology, 2007)
An analysis of internal transcribed spacer (ITS) DNA sequences of the four species of Carum L. (Apiaceae) known in Italy revealed that this genus is polyphyletic. Maximum parsimony with bootstrap resampling, maximum likelihood and Bayesian inference analyses resulted in three distinct clades: Carum carvi L. clustered within tribe Careae Baill. (former Aegopodium clade); Hellenocarum multiflorum (= Carum multiflorum), Carum heldreichii and Carum appuanum clustered within the tribe Pyramidoptereae Boiss.; and H. multiflorum and C. heldreichii formed a well supported clade. Since the sister group of H. multiflorum and C. heldreichii was Bunium elegans the autonomy of Hellenocarum from Carum is confirmed by our study. We also found that C. appuanum clustered separately from the other Carum species, with the closest related species appearing to be Scaligeria moreana but this still had few morphological similarities with C. appuanum.